Computed Tomography-Based Evaluation of Volume and Position Changes of the Target Region and Organs at Risk During Radiotherapy for Esophageal Cancer: A Pilot Study - Liu, Yi-mei; Peng, Ying-lin; Li, Qi-wen; Shen, Guanzhu; Ma, Ya-ru; Chen, Mei-ning; Zhang, Jun; Fu, Li-rong; Qiu, Bo; Liu, Hui; Deng, Xiao-wu (Frontiers in Oncology, 2021)
Objective: To analyze changes in volume and position of target regions and organs at risk (OARs) during radiotherapy for esophageal cancer patients. Methods: Overall, 16 esophageal cancer patients who underwent radiotherapy, including 10 cases of intensity-modulated radiation therapy (IMRT) and six of three-dimensional conformal radiotherapy (3D-CRT), were enrolled. The prescription doses for the planning target volumes (PTVs) were as follows: PTV1, 64 Gy/32 fractions and PTV2, 46 Gy/23 fractions. Repeat computed tomography (CT) was performed for patients after the fifth, tenth, fifteenth, twentieth, and twenty-fifth fractions. Delineation of the gross tumor volume (GTV) and OAR volume was determined using five repeat CTs performed by the same physician. The target and OAR volumes and centroid positions were recorded and used to analyze volume change ratio (VCR), center displacement (ΔD), and changes in the distance from the OAR centroid positions to the planned radiotherapy isocenter (distance to isocenter, DTI) during treatment. Results: No patient showed significant changes in target volume (TV) after the first week of radiotherapy (5 fractions). However, TV gradually decreased over the following weeks, with the rate slowing after the fourth week (40 Gy). The comparison of TV from baseline to 40 Gy (20 fractions) showed that average GTVs decreased from 130.7±63.1 cc to 92.1±47.2 cc, with a VCR of -29.21%±13.96% (p<0.01), while the clinical target volume (CTV1) decreased from 276.7±98.2 cc to 246.7±87.2 cc, with a VCR of -10.34%±7.58% (p<0.01). As TVs decreased, ΔD increased and DTI decreased. After the fourth week of radiotherapy (40 Gy), centroids of GTV, CTV1, and prophylactic CTV (CTV2) showed average deviations in ΔD of 7.6±4.0 mm, 6.9±3.4 mm, and 6.0±3.0 mm, respectively. The average DTI of the heart decreased by 4.53 mm (from 15.61±2.96 cm to 15.16±2.27 cm). Conclusion: During radiotherapy for esophageal cancer, Targets and OARs change significantly in volume and position during the 2nd-4th weeks. Image-guidance and evaluation of dosimetric changes is recommended for these fractions of treatment to appropriate adjust treatment plans.